Toward the identification of neuroprotective agents: g-scale synthesis, pharmacokinetic evaluation and CNS distribution of (R)-RC-33, a promising SIGMA1 receptor agonist. (March 2016) - Marra, Annamaria; Rossi, Daniela; Pignataro, Luca; Bigogno, Chiara; Canta, Annalisa; Oggioni, Norberto; Malacrida, Alessio; Corbo, Massimo; Cavaletti, Guido; Peviani, Marco; Curti, Daniela; Dondio, Giulio; et al.
Aim: Nowadays, there is a great interest in the therapeutic potential of sigma1 receptor ligands for treating different CNS pathologies. Our previous investigations led to identify ( R )-RC-33 as a potent and selective S1R agonist.Results: Herein, we report the gram-scale synthesis, pharmacokinetic profile and CNS distribution of ( R )-RC-33 in the mouse to determine the most suitable dosage schedule for in vivo administration. For comparative purposes, the same experiments were also performed with PRE-084, the most widely used S1R agonist commonly in pharmacological experiments.Discussion: ( R )-RC-33 shows a similar pharmacokinetic profile and a better CNS distribution when compared with PRE-084.Conclusion: ( R )-RC-33 may be a promising candidate for in vivo studies in animal models of neurodegenerative diseases.